Dampak Program Enhancement dan Work Engagement Terhadap Kinerja Karyawan Bank Jatim - Andreas Kristanto Nahot; I Nyoman Sutapa (Jurnal Titra, 2022)
Performance is influenced by individual ability and work engagement. To improve the ability of its employees, Bank Jatim provides a program called enhancement. Based on the annual report of Bank Jatim, the program assessment given is only limited to pre-test and post-test, which if the post-test score is high then the employee is considered good. Therefore, this study aims to determine whether the enhancement and work engagement programs have an effect on employee performance and a description of the work engagement of Bank Jatim employees. The data used in this study is the KPI balanced scorecard from the perspective of learning and growth and finance and questionnaires distributed to 54 employees in all branches throughout East Java. After all the data was collected, the data was analyzed descriptively using the Structural Equation Modeling (SEM) method to determine the effect between variables. The results of this study are enhancement programs have an impact on employee performance but work engagement has no impact on employee performance. In addition, the description of work engagement shows that the majority of employees who get high engagement scores come from employees who have worked under 5 years.